2014
DOI: 10.1164/rccm.201405-0973oc
|View full text |Cite
|
Sign up to set email alerts
|

Body Composition and Mortality after Adult Lung Transplantation in the United States

Abstract: Rationale: Obesity and underweight are contraindications to lung transplantation based on their associations with mortality in studies performed before implementation of the lung allocation score (LAS)-based organ allocation system in the United States Objectives: To determine the associations of body mass index (BMI) and plasma leptin levels with survival after lung transplantation.Methods: We used multivariable-adjusted regression models to examine associations between BMI and 1-year mortality in 9,073 adult… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
102
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2
2

Relationship

2
7

Authors

Journals

citations
Cited by 118 publications
(107 citation statements)
references
References 56 publications
3
102
2
Order By: Relevance
“…We previously demonstrated that preoperative underweight status and hypoalbuminemia are strongly associated with mortality after lung transplant (34,56). Also, low lean muscle mass sarcopenia is common in patients with COPD and in lung transplant candidates (34,47). Consistent with these reports, lean muscle mass correlated with both of the frailty measures used in this study.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…We previously demonstrated that preoperative underweight status and hypoalbuminemia are strongly associated with mortality after lung transplant (34,56). Also, low lean muscle mass sarcopenia is common in patients with COPD and in lung transplant candidates (34,47). Consistent with these reports, lean muscle mass correlated with both of the frailty measures used in this study.…”
Section: Discussionsupporting
confidence: 89%
“…For example, low BMI and hypoalbuminemia are associated with both frailty and sarcopenia (presumably because abnormally low lean muscle mass and function is a putative driver of the frail phenotype) (29,40,42,54,55). We previously demonstrated that preoperative underweight status and hypoalbuminemia are strongly associated with mortality after lung transplant (34,56). Also, low lean muscle mass sarcopenia is common in patients with COPD and in lung transplant candidates (34,47).…”
Section: Discussionmentioning
confidence: 99%
“…The previous studies have identified an association between obesity and an increased risk of PGF [18,19]. Singer et al suggested that adiposity is associated with inflammatory adipokines and other cytokines, which can cause PGF [20]. Several cytokines and chemokines have been found to be associated with PGF [21,22].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, obesity was associated with an increased mortality rate after LTx. However, another study suggested that obesity is not associated with 1-year mortality after LTx, and a BMI greater than 30 kg/m 2 may no longer represent a contraindication (28). Overall, controversy surrounds interpretation the relationship between obesity and survival rates in LTx patients.…”
Section: Discussionmentioning
confidence: 99%